2022
DOI: 10.5435/jaaos-d-21-00612
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hazards for the Practicing Orthopaedic Surgeon: A Standard Review

Abstract: Orthopaedic surgeons are exposed to various occupational hazards in a busy daily practice which can cause potential physical injury and additional mental stress. By better understanding the hazards that are faced in the operating theater and the preventive measures that can be taken to avoid injury, orthopaedic surgeons can remain effective in their patient care duties. Infectious exposures, radiation exposure, noise pollution, chemical hazards, and physical demands are frequently encountered at the time of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Increased rates of LET and other musculoskeletal conditions among orthopaedic surgeons have been described previously in the literature. [35][36][37] In our study male volunteers appeared almost twice as likely to have asymptomatic MRI findings than females (Table 5). This is contrary to several population studies which have shown a higher prevalence of symptomatic LET in females than males, [38][39][40] despite others suggesting there is no significant association between LET and sex.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Increased rates of LET and other musculoskeletal conditions among orthopaedic surgeons have been described previously in the literature. [35][36][37] In our study male volunteers appeared almost twice as likely to have asymptomatic MRI findings than females (Table 5). This is contrary to several population studies which have shown a higher prevalence of symptomatic LET in females than males, [38][39][40] despite others suggesting there is no significant association between LET and sex.…”
Section: Discussionsupporting
confidence: 47%
“…Increased rates of LET and other musculoskeletal conditions among orthopaedic surgeons have been described previously in the literature. 3537…”
Section: Discussionmentioning
confidence: 99%